Wind Measurements for Optimal Siting, construction and Operation of Offshore Wind Farms with Synthetic Aperture Dadar - Lehner, Susanne; Horstmann, Jochen; Schneiderhan, Tobias; Schulz-Stellenfleth, Johannes (2003)
In all European countries with shallow coastal waters and strong mean wind speed at the coast the planning and construction of offshore wind farms is on the way and large parts of the North Sea and the Baltic are under investigation as to whether they are suitable for offshore parks. In this paper it is demonstrated how satellite images taken by spaceborne radar sensors can be used to determine mesoscale wind fields and thus help in the task of planning offshore wind farms. High resolution SAR images acquired by the European remote sensing satellite ERS 2 are presented which show single wind turbines (Fig. 1). The derivation of high resolution wind fields from SAR images is explained and comparisons with numerical models are presented.